Plasminogen-activator-inhibitor-1 promoter polymorphism as a risk factor for adult periodontitis in non-smokers - Izakovicová Hollá, L; Bucková, D; Fassmann, A; Benes, P; Znojil, V (Genes and immunity, 2002)
Periodontal diseases belong to the most common chronic disorders affecting mankind. Smoking and impaired plasminogen activation with hypercoagulation and fibrinolysis inhibition have been proposed as having a role in predisposition to these diseases. We investigated relationships among adult periodontitis, smoking, and a variation in the deletion/insertion (4G/5G) promoter polymorphism of the plasminogen-activator-inhibitor-1 (PAI-1) gene in 304 Caucasian subjects. An association was detected between the deletion (4G) allele (and 4G/4G genotype) and periodontitis (P = 0.0022, P(corr) < 0.01; P = 0.014, P(corr) < 0.05). A stronger association occurred in non-smokers (P = 0.00021, P(corr) < 0.01; P = 0.0024, P(corr) < 0.05) where the presence of the PAI-1 gene 4G allele appears to be one of the risk factors for periodontitis.
Keywords: alely; kouření; Periodontitis; genotyp; Alleles; Genotype; Middle Aged; Promoter Regions, Genetic; mužské pohlaví; genetická variace; parodontitida; Adult; Sequence Deletion; polymorfismus genetický; sekvenční delece; Genetic Variation; Smoking; Polymorphism, Genetic; ženské pohlaví; Humans; lidé středního věku; inhibitor aktivátoru plazminogenu 1; promotorové oblasti (genetika); rizikové faktory; Plasminogen Activator Inhibitor 1; dospělí; Female; Risk Factors; lidé; Male